Manjericão (Ocimum basilicum L.) sob diferentes períodos de estresse salino: fitomassa, fitoquímica e citogenotoxicidade - Kuhn, Andrielle Wouters (2018)
Basil has aroused biological, pharmacological, agronomic and industrial interests, and stand out in the essential oil production. This study aimed to evaluate the production of biomass and essential oil of basil plants (Ocimum basilicum L. “Basilicão”) in protected cultivation without ground under different periods of induction to saline stress, and, also, analyze the phytochemical composition and the cytogenetoxicity of aqueous extracts and essential oil of this cultivated plants. The experiments in the greenhouse (during summer and winter) were conducted at the Department of Plants Sciences of the Federal University of Santa Maria, Brazil, in the course of the year of 2016, evaluating four different periods of induction to saline stress (0, 10, 20 and 30 days). Were analyzed the following variables: fresh weight (MF) and dry matter (MS) (leaves, stems and flowers), number of inflorescences (NI), oil yield (ROE) and its phytochemical, besides the cytogenetoxicity analysis of plants aqueous extracts and essential oil through the Allium cepa L. test. The experiments were conducted through a completely randomized design, and data were subjected to varianceanalysis. Those relating to biomass production, essential oil yield and chromatography, were analyzed by polynomial regression, while those regarding the evaluation of cytogenetoxicic potential of essential oil and aqueous extracts were compared by Scott-Knott test (p <0.05). MF and MS, of leaves and stems, and MF of the total aerial part reduce with the application of periods of induction to saline stress (5 dSm-1), both in summer and winter. While MF, MS and number of inflorescences increase in the summer season, no loss or increment of MF, MS and number of inflorescences in the winter, and of MS of the total aerial part were observed in the two growing seasons. Leaf ROE, in summer and winter, and total ROE decrease, while ROE of inflorescences, in summer, increases with the periods studied. The linalool is the major compound of essential oil and its amount is increased under the induction to saline saline stress. The effects observed in cytogenetoxicity analysis of basil aqueous extracts and essential oil, are not associated with periods of induction to saline stress. And the extracts prepared with inflorescences of plants grown only on standard nutrient solution (1 dSm-1), reduced the cell proliferation of A. cepa cells, indicating a cytotoxic effect, the antiproliferative activity for the extracts of the inflorescences of the plant in the concentration of 10 g L-1. The compounds found in higher concentrations in these extracts are: rosmarinic acid, caffeic acid and quercetin.